(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2024)
In the article determined the increasing of quota of criatinin total quality of extra term nitrogen. Index of creatin (9,1) shows to presence of protein energetic insufficiency in sportsmen. That is the base of optimization of norm of nutrition of the given group of sportsmen